Spatial and Temporal Characteristics of Cirrus Clouds over the Tibetan Plateau Based on CALIPSO and AIRS Observations - Hailei Liu; Yuan Chen; Shenglan Zhang; Jilie Ding; Xiaobo Deng; Xingzhong Liu (Advances in Meteorology)
The spatial and temporal distribution characteristics of high clouds over the Tibetan Plateau (TP) were studied using the Atmospheric Infrared Sounder (AIRS) and the GCM-Oriented CALIPSO Cloud Product (CALIPSO-GOCCP) monthly mean cloud products from 2007 to 2017. The high clouds over the TP are dominated by cirrus and show seasonal variation characteristics. There were two distinct areas with the high occurrence of cirrus clouds in the area (0°–60°N, 75°–103°E). One was located in the regions from the equator to 25°N, and the other was within the latitude belt from 30° to 40°N. From January to May, cirrus clouds mainly occurred in the central and northern parts of the TP (30° to 40°N), and the cirrus cloud fraction increased from January and reached its maximum (∼0.51) in April. From June to August, cirrus clouds mainly occurred in the southern part of the TP during summer. The cirrus clouds over the southern TP were relatively high (located in 10–17 km) and manifested northward and southward movements. The ice clouds in the southern TP are associated with plateau deep convection activities and abundant vapor transmitted by the Asian monsoon. Cirrus clouds over the northern and central TP may be relevant to the atmospheric lift by an approaching cold front and topographic lifting. Moreover, the high clouds below 11 km are dominated by opaque clouds, while the nonopaque (or thin) and opaque (or thick) clouds above 11 km are comparable.